If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3x = 2 + 8x Add '-2' to each side of the equation. 2 + -2 + 3x = 2 + -2 + 8x Combine like terms: 2 + -2 = 0 0 + 3x = 2 + -2 + 8x 3x = 2 + -2 + 8x Combine like terms: 2 + -2 = 0 3x = 0 + 8x 3x = 8x Solving 3x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 3x + -8x = 8x + -8x Combine like terms: 3x + -8x = -5x -5x = 8x + -8x Combine like terms: 8x + -8x = 0 -5x = 0 Divide each side by '-5'. x = 0 Simplifying x = 0
| 2cosx*sinx=0 | | 0=3(7N+30+4M) | | -8-8x=104-29x | | 4+2+-1+-3= | | 10b-4=44 | | 5+3x=2+8x | | 3x(x+1)=42 | | 5+3x=2+10x | | 30-7c=10c-4 | | 5+3x=2+6x | | 3/4x+26=18 | | 4x-5x^2/x | | 2x-3(1)=-7 | | 26-3/4x=18 | | 5-3x=84+6x | | 12+14=3*f | | 5-3x=4+6x | | 6-8(5-3x)=0 | | 52+g=45+11 | | 2-6x=4+8x | | 4(6x-7)=32x | | 2-6x=14+8x | | z-51/6=116/7 | | 37+s=80/2 | | 3y-12x=18 | | H=16t^2-180t | | 2-3x=4+10x | | (3+2-2-1)(4+-1+-3)= | | 2-3x=4+8x | | 420/d=30 | | 2-3x=14+8x | | 5-3x=14+4x |